Structural and computational analysis of a nickel(II) complex with S-benzyldithiocarbazate Schiff base ligand: synthesis, x-ray crystallography, MEP, HOMO-LUMO, Hirshfeld surface analysis, and molecular docking - Mohamed Tahir, Mohamed Ibrahim; Osman, Uwaisulqarni M.; Noor Hassim, Muhamad Fairus; Zaini Safayi, Nik Nur Syafiqah; Arshad, Suhana; Mohd Nizar, Siti Nabilla Aliya; Abdul Razak, Fazira Ilyana; Sapari, Suhaila (Elsevier B.V., 2025)
A new compound, benzyl N-[1-(thiophen-2-yl)propylidene]hydrazinecarbodithioate (LH), and its nickel(II) complex (NiL2), were synthesized and structurally identified. Single crystal X-ray diffraction analyses determined that both the LH ligand and the NiL2 complex crystallized in the monoclinic system, with space group P21/c and Z = 4. The LH ligand exhibited lattice parameters of a = 9.661(2)Å, b = 8.995(2)Å, c = 18.939(4)Å, β = 102.677(4)°, V = 1605.7(7)Å3, whereas, NiL2 exhibited a = 17.805(7)Å, b = 10.548(4)Å, c = 18.100(7)Å, β = 108.279(6)°, V = 3228(2)Å3. The NiL2 complex was found to possess a slightly distorted square planar geometry with the LH deprotonated ligand acting as a monoanionic bidentate by coordinating through the azomethine nitrogen and thiolate sulfur atoms. It was observed that the HOMO-LUMO energy gap of the NiL2 complex (0.3654 eV) was lower than that of the LH ligand (2.4425 eV), indicating that NiL2 possesses a higher reactivity than the LH ligand. Intermolecular hydrogen bonding interactions were examined by Hirshfeld surface and 2D fingerprint analysis, which showed predominant H…H interactions for both the LH ligand and the NiL2 complex. A molecular docking simulation study with the dopamine D4 receptor (DRD4) and farnesyltransferase (FTase) revealed that NiL2 was able to interact with 13 residues in FTase, as compared to the farnesyl-Cys drug interacted with 11 residues.